THE IMPACT ANALYSIS OF ASEAN-JAPAN COMPREHENSIVE ECONOMIC PARTNERSHIP (AJCEP) FOR TRADE FLOW AND ECONOMIC GROWTH’S CONVERGENCE - Tri Arifin Darsono; Dedi Budiman Hakim; Wiwiek Rindayati (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2015)
Free Trade Area (FTA) between ASEAN and Japan, which is called ASEAN-Japan Comprehensive Economic Partnership (AJCEP), has been established since 2002 as goods and services flow gateway. AJCEP plays an important role to bring the development, economic security, and economic power. It can also boost the economic growth among member of ASEAN-Japan. The objectives of this research were to analyze the factors that can influence the ASEAN-Japan countries import with non-member, to analyze the occurrence of trade creation and trade diversion in trading sector among ASEAN-Japan countries with non-member, and to analyze the occurrence of economic growth's convergence in ASEAN-Japan Comprehensive Economic Partnership (AJCEP) not only among ASEAN-Japan countries, but also with non-member trading partners. The Gravity Model was used to analyze import factors and observing the occurrence of trade creation or trade diversion. The GMM model was used to observe the convergence of economic growth. The research are used Panel data methods with periods 2000 until 2013 in 13 countries.      The research found that the coefficient values in trade creation and trade diversion dummy were 0.92 and 31.41. The positive value in trade creation and trade diversion indicated the occurrence of trade creation in the import flow among ASEAN-Japan countries and non-member trading partners, as well as finding the convergence of economic growth among ASEAN-Japan countries. The convergence level was of 0.0153417 can be interpreted that the velocity to reach steady state condition was 2.00 percent per year with the assumption of ceteris paribus. The duration to reach convergence condition or half life of convergence was about 34 years. The research found the trade creation from AJCEP agreement and the occurrence of economic growth’s convergence. Based on the result, Indonesian government would likely to make relationships among countries member and non-member to invest in real sector that will boost economic growth in Indonesia. Keywords: ASEAN-Japan Comprehensive Economic Partnership, Growth’s convergence, gravity model, GMM model, trade creation, trade diversion.